Beyond public acceptance of energy infrastructure: How citizens make sense and form reactions by enacting networks of entities in infrastructure development. (September 2016) - Aaen, Sara Bjørn; Kerndrup, Søren; Lyhne, Ivar
Abstract: This article adds to the growing insight into public acceptance by presenting a novel approach to how citizens make sense of new energy infrastructure. We claim that to understand public acceptance, we need to go beyond the current thinking of citizens framed as passive respondents to proposed projects, and instead view infrastructure projects as enacted by citizens in their local settings. We propose a combination of sensemaking theory and actor–network theory that allows insight into how citizens enact entities from experiences and surroundings in order to create meaning and form a reaction to new infrastructure projects. Empirically, we analyze how four citizens make sense of an electricity cable project through a conversation process with a representative from the infrastructure developer. Interestingly, the formal participation process and the materiality of the cable play minor roles in citizens' sensemaking process. We conclude that insight into the way citizens are making sense of energy infrastructure processes can improve and help to overcome shortcomings in the current thinking about public acceptance and public participation. Highlights: Attention to citizens' sensemaking enables greater insight into the decision-making process. A combination of sensemaking and actor-network theory (ANT) is relevant for studies of public acceptance. Sensemaking explains why citizens facing similar situations act differently. Complexity of citizens' sensemaking challenges the predictability of processes.